Trimmed-mean inflation statistics: Just hit the one in the middle - Brent Meyer; Guhan Venkatu (Federal Reserve Bank of Atlanta, 2014)
This paper reinvestigates the performance of trimmed-mean inflation measures some 20 years since their inception, asking whether there is a particular trimmed-mean measure that dominates the median consumer price index (CPI). Unlike previous research, we evaluate the performance of symmetric and asymmetric trimmed means using a well known equality of prediction test. We find that there is a large swath of trimmed means that have statistically indistinguishable performance. Also, although the swath of statistically similar trims changes slightly over different sample periods, it always includes the median CPI - an extreme trim that holds conceptual and computational advantages. We conclude with a simple forecasting exercise that highlights the advantage of the median CPI (and trimmed-mean estimators in general) relative to other standard measures in forecasting headline inflation.
Keywords: E31; E37; 330; inflation; inflation forecasting; trimmed-mean estimators